Cooperative dairy development in Karnataka, India: an assessment - Alderman, Harold (International Food Policy Research Institute, 1987)
The Karnataka Dairy Development Project was inaugurated in 1974 with the assistance of the World Bank. It is an example of an approach to agricultural development that emphasizes integrating rural households into a market economy by incrasing the use of purchased inputs and increasing the marketed surplus. Such approaches have been controversial because it is alleged that the commercialization of agriculture that is a part of the approach worsens the distribution of income and the nutrition of the local population. The evidence available about such approaches is scant, even though the Karnataka project is modeled closely on the larger Operation Flood dairy development project, which has been at the center of these debates.